Exploring the resource value of transvaal red milk wood (Mimusops zeyheri) for food security and sustainability: An appraisal of existing evidence - Omotayo, Abiodun Olusola; Ijatuyi, Enioluwa Jonathan; Ogunniyi, Adebayo; Aremu, Adeyemi Oladapo (MDPI, 2020)
Many African countries are endowed with rich biodiversity with enormous nutritional and economic prospects, but the majority of these resources are not fully harnessed. Exploring these neglected resources, for example, the Transvaal red milkwood tree [(Mimusops zeyheri) Sond. family: Sapotaceae] is of paramount importance for food and nutritional security as well as economic prosperity. This review provides a critical appraisal of the nutritional and health benefits as well as the economic potential of Mimusops zeyheri. The plant is known for its diverse uses among rural communities. In folk medicine, the decoction from the bark and leaves of Mimusops zeyheri are used for treating wounds and ulcers, while the root is used as an infusion taken to treat candidiasis and other health issues. The nutritional profile of the fruit tree is similar to popular exotic fruits and richer in vitamin C when compared to guava and orange. Mimusops zeyheri is a rich source of vitamins, protein, and fatty acids. Based on the rich chemical pool, especially in the fruit and seeds, it has the potential to provide an accessible, readily available, and affordable enriched functional food with valuable health benefits. However, the successful exploration of Mimusopszeyheri for food security and sustainability requires multidisciplinary research. This will help achieve the envisaged food-nutrition security and poverty alleviation potential of the plant, especially among local communities.